Sejarah Sanad Ilmu Al-Qur’an di Kalangan Ulama Minangkabau dan Perannya sebagai Basis Epistemologi Pendidikan Islam - Jemmy Harto (PT. Student Rihlah Indonesia, 2026)
This study aims to analyze the role of sanad as an epistemological foundation in Islamic education through an examination of the transmission of Qur’anic knowledge among Minangkabau ulama. In the Islamic intellectual tradition, sanad does not merely function as a chain of transmission but also as a mechanism for validating the authority of knowledge, ensuring the authenticity and continuity of teachings. This research employs a qualitative approach using historical methods and intellectual genealogy analysis to examine the chains of qira’at transmission that developed in Minangkabau, particularly through the figures of Syeikh Yasin Al-Fadani, Syeikh Ahmad Khatib Al-Minangkabawi, Syeikh Abdurrahman Al-Khalidi Batuhampar, and Syeikh Abdurrauf Singkil. The findings reveal that sanad functions as an epistemic system that integrates oral transmission, scholarly authority, and global networks of ulama centered in the Haramain. Minangkabau ulama not only act as recipients of the intellectual tradition but also as agents of sanad dissemination, contributing to the formation of Islamic educational networks in the Malay-Indonesian world and beyond. Furthermore, the existence of qira’at manuscripts and the practice of talaqqi demonstrate a combination of textual and oral transmission in preserving the authenticity of Qur’anic knowledge. This study concludes that sanad constitutes a foundational epistemology in Islamic education, maintaining enduring relevance in safeguarding the integrity of knowledge while highlighting the strategic position of Minangkabau ulama within the global intellectual network of Islam.